2011
DOI: 10.1093/jac/dkr344
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of the efficacy and safety of sequential intravenous/oral moxifloxacin monotherapy versus intravenous piperacillin/tazobactam followed by oral amoxicillin/clavulanate for complicated skin and skin structure infections

Abstract: ObjectivesThe primary aim of the RELIEF study was to evaluate the efficacy and safety of two sequential intravenous (iv)/oral regimens: moxifloxacin iv/oral versus piperacillin/tazobactam (TZP) iv followed by oral amoxicillin/clavulanate (AMC).Patients and methodsThe study had a prospective, randomized, double-dummy, double-blind, multicentre design. Patients ≥18 years were prospectively stratified according to complicated skin and skin structure infection (cSSSI) subtype/diagnosis (major abscess, diabetic foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 38 publications
2
46
0
9
Order By: Relevance
“…DFI was the most frequent diagnosis in the Asia–Pacific region and patients there had longer response times in comparison with the other regions. Data from randomized clinical trials have shown that moxifloxacin achieves clinical cure in 79–82% of patients with cSSSIs [1618, 24], rates that are comparable with the results obtained in the ARTOS study. As mentioned above, the majority of investigators in the ARTOS study have rated the overall effectiveness of moxifloxacin as ‘very good’ or ‘good.’ Based on the type of diagnosis it was found ‘very good’ or ‘good’ in 82.6% of DFI and 86.4% of infected ulcer patients, while the effectiveness was rated similarly for a higher proportion of patients with abscesses (94.5%) or wound infections (92–96.1%).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…DFI was the most frequent diagnosis in the Asia–Pacific region and patients there had longer response times in comparison with the other regions. Data from randomized clinical trials have shown that moxifloxacin achieves clinical cure in 79–82% of patients with cSSSIs [1618, 24], rates that are comparable with the results obtained in the ARTOS study. As mentioned above, the majority of investigators in the ARTOS study have rated the overall effectiveness of moxifloxacin as ‘very good’ or ‘good.’ Based on the type of diagnosis it was found ‘very good’ or ‘good’ in 82.6% of DFI and 86.4% of infected ulcer patients, while the effectiveness was rated similarly for a higher proportion of patients with abscesses (94.5%) or wound infections (92–96.1%).…”
Section: Discussionsupporting
confidence: 69%
“…When comorbidities were taken into account regarding DFI patients, which may influence the length of therapy and clinical outcome, we have observed a similar result to that for the DFI patients enrolled in the RELIEF trial which was a randomized, double-blind study [18, 24]. Thus, comparing patients enrolled in the RELIEF and ARTOS studies regarding specific comorbidities of DFI patients, the proportion of patients with peripheral vascular disease (>65.5 vs 55.7%, respectively), peripheral neuropathy (49.5 vs 63.5%, respectively), or osteomyelitis (20 vs 28.8%, respectively) were rather similar.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The rationale of the RELIEF study was to provide additional data on the efficacy and safety of MXF in four specific cSSSI diagnoses (major abscess, DFI, wound infection, infected ischemic ulcer) [22]; the present paper reports on the efficacy and safety of MXF versus a β-lactam/β-lactamase inhibitor combination in the subgroup of patients with DFI. The RELIEF study is unique in that it addresses the limitations of previous studies by stratification at inclusion, according to the severity of cSSSI and baseline surgery.…”
Section: Introductionmentioning
confidence: 99%
“…These features are especially needed in DFI. There is evidence of MXL utility in the treatment of DFI, with similar results to piperacillin–tazobactam followed by amoxicillin–clavulanate, even in patients with major vascular involvement (ischemic) or structural (large or profound ulcers),6062 because it keeps antimicrobial concentrations in the perinecrotic tissue above the MIC 63. DLX provides over MXL the activity against MRSA and its diffusion in acid mediums, as is frequent in diabetic foot ischemia.…”
Section: Efficacymentioning
confidence: 91%